2002
DOI: 10.1093/hmg/11.12.1449
|View full text |Cite
|
Sign up to set email alerts
|

Promoter switch: a novel mechanism causing biallelic PEG1/MEST expression in invasive breast cancer

Abstract: We have previously reported on the biallelic expression of the imprinted PEG1/MEST gene in infiltrating carcinomas of the breast. Putative loss of imprinting (LOI) of PEG1/MEST has subsequently also been implicated in the aetiology of lung adenocarcinomas and colon cancer. Taking advantage of our previous study, identifying seven infiltrating carcinomas of the breast, displaying biallelic PEG1/MEST expression, we have analysed the allelic usage of the two alternative PEG1/MEST transcripts encoding isoforms 1 a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(40 citation statements)
references
References 16 publications
2
38
0
Order By: Relevance
“…ARMCX2 might have a role in tumour suppression based on the presence of an armadillo repeat motif, which is found in other proteins fulfilling functions in cell proliferation, migration, maintenance of tissue integrity and tumourigenesis, and has been involved in development (Smith et al, 2005). MEST, a maternally imprinted gene, has been implicated in embryonic growth and maternal behaviour (Lefebvre et al, 1998), and loss of MEST imprinting has been reported in breast and lung cancers (Pedersen et al, 2002;Nakanishi et al, 2004). Interestingly, it has recently been shown that MEST is a negative regulator of the Wnt pathway and that MEST knockdown might activate Wnt signalling (Jung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…ARMCX2 might have a role in tumour suppression based on the presence of an armadillo repeat motif, which is found in other proteins fulfilling functions in cell proliferation, migration, maintenance of tissue integrity and tumourigenesis, and has been involved in development (Smith et al, 2005). MEST, a maternally imprinted gene, has been implicated in embryonic growth and maternal behaviour (Lefebvre et al, 1998), and loss of MEST imprinting has been reported in breast and lung cancers (Pedersen et al, 2002;Nakanishi et al, 2004). Interestingly, it has recently been shown that MEST is a negative regulator of the Wnt pathway and that MEST knockdown might activate Wnt signalling (Jung et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…41 Subsequent reports have indicated that in certain tissues including breast, placenta and colon, isoform 2 may in fact be imprinted and, moreover, that the imprinting status (whether monoallelic or biallelic) may differ between individuals. 13,16,37,47 Isoform 2 has been observed to be preferentially paternally expressed in foetal placenta in other studies, and also in kidney and fibroblast lines, with polymorphic imprinting observed between different fibroblast lines. 48 Variable imprinting of MEST, including that of isoform 2, has also been reported between humanembryonic stem cell (hESCs) lines, raising concerns of the epigenetic stability of these cells.…”
Section: Discussionmentioning
confidence: 57%
“…48 Variable imprinting of MEST, including that of isoform 2, has also been reported between humanembryonic stem cell (hESCs) lines, raising concerns of the epigenetic stability of these cells. 40,49,50 In view of the observations of aberrant MEST methylation and imprinting with disease, 13,14,16 we considered it important to further characterise expression at the MEST locus in the embryos with expression arising from both alleles. Our data demonstrates that isoform 2 was the predominant MEST isoform detected in preimplantation embryos and show directly that imprinting of isoform 2 itself is variable between embryos (Figure 4d).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations